(untitled) (Respirar, 2026)
Introduction: The use of noninvasive ventilation (NIV) and continuous positive airway pressure (CPAP) in general wards allows for early intervention in patients with acute respiratory failure (ARF), reducing complications associated with intensive care unit (ICU) admission, freeing ICU beds, and lowering healthcare costs. However, its implementation remains limited. Objective: To describe the characteristics and clinical outcomes of patients with hypercapnic acute respiratory failure (ARF-HC) treated with NIV/CPAP in general wards of a public general hospital in Buenos Aires, Argentina. Materials and methods: A retrospective analysis of protocolized records since 2010. Patients admitted with ARF-HC and arterial pH between 7.25 and 7.46 were evaluated for NIV/CPAP. CPAP was primarily indicated for patients with decompensated obstructive sleep apnea (OSA). Demographic data, comorbidities, days of NIV use and hospitalization, treatment success (discharge) or failure (intubation/death), and complications were recorded. Results: Fifty-two patients were treated in 64 episodes, between 2010-2023. Mean age: 57 years (SD13.4); 55.8%: female. Common comorbidities: smoking (46.1%), obesity (25%), COPD (20.6%), and neuromuscular disease (23.1%). Main indications for NIV/CPAP: neuromuscular disease and chest wall disorders (18.75% each), COPD and heart failure (12.5% each). Median NIV duration: 6 days; median hospital stay, 10 days. No hospital-acquired infections were observed. Overall success rate: 87.5%; failure rate: 12.5% (50% of failures resulting in death). Conclusions: NIV and CPAP use in general wards proved to be safe and effective for managing ARF-HC, with a high success rate and no nosocomial infections. Expansion of equipment and staff training is essential to extend its use.